Program pendidikan pencegahan dadah SLAD: adakah ia berkesan mencapai matlamatnya? - Mohamed, Mahmood Nazar; Don, Yahya; Hassan, Mohamad; Kasa, Muhamad Dzahir (UUM College of Arts and Sciences, 2005)
Drug prevention education has become a critical issue in schools today because there is an increase in youth involvement with drugs. Although the number of youths addicted to narcotics and other serious substances is not significantly high, those experimenting with tobacco, recreational drugs, thinners and glues are on the rise. This is evident by statistics provided by the National Drugs Agency.One strategy to increase drug awareness and build adequate defenses against drug taking behavior is drug education among school children. An innovative approach currently used in Malaysia is the Skim Lencana Anti Dadah or SLAD. This program targets youths aged 16 or 10th grade equivalence to a program that aims to increase their knowledge and awareness about drugs, and for them to act as peer support for other vulnerable youths. This study uses a pre-post test design, similar group comparison between schools with and without the SLAD. It evaluates the outcome of this program in terms of knowledge about drugs and their self-esteem. The study found that youths who undergo the SLAD program show a significant increase in knowledge on drugs not only immediately after the program but also six months later. They also scored significantly higher on self-esteem when compared to the control group. This shows that the SLAD drug education program has successfully increased their knowledge on drugs and their self-esteem, which will enable them to be aware of the danger of drugs and be confident enough to assist their peers to also stay away from drugs.